Analisis Pemborosan Waktu Produksi Pada Proses Pembuatan Melting Pot Menggunakan Pendekatan Lean di PT. KARYA ILHAM MANDIRI - meckel rifaldo, mohammad; Abryandoko, Eko Wahyu (Jurnal Teknologi dan Manajemen Sistem Industri, 2023)
Supply chain management combines all parties involved in the manufacture of products, either directly or indirectly. A quality management tool known as Value Stream Mapping (VSM) has the ability to match the current state of a process by providing opportunities for improvement and reducing waste. To create a Value Stream Mapping (VSM), some building symbols are needed. Each symbol in VSM serves a different purpose and serves a different purpose. They also show the various stakeholders involved in the process and explain the processes that occur. Future State Value Stream Mapping shows the results of proposed improvements that can reduce Non Value Added by 37.84%. Based on the identification of the Home Industry Supply Chain process, the result of proposed future improvements that eliminate non-value-added time is expected to reduce the value to 37.84%.